Hindering the Development of the Jury Trail in Russian Federation and the Problems of Court Independence - Gubaidullina, Elvira; Gubaidullin, Artur (Journal of History Culture and Art Research, 2018)
The relationship between the judiciary power and the jury is historically not simple in Russia. Despite the fact that after a long period of oblivion, this institution was returned still to the domestic legislation, the attitude to it continues to be ambiguous. This article attempts to find out the reasons for this state of affairs. Based on the analysis of modern scientific literature reflecting the opinions of practical employees of the judiciary power, such reasons are summarized in the appropriate categories: organizational, technical, material, personnel, psychological, procedural and political. In more detail, the article considered the material and the political circumstances. And if almost all studied sources focus their attention on the material aspect, the political reasons that impede the development of the jury trial in RF are similar to the hidden part of the iceberg: they are also large and hidden. The work emphasizes the need for a jury trial, the stabilization of the legislation developing it and its popularization among the population. Based on the results of the analysis, the main conclusion is drawn that the judiciary power in Russian Federation suffers from the process of power centralization, and thus it often fulfills the political will of the state.